2002
DOI: 10.1136/emj.19.5.400
|View full text |Cite
|
Sign up to set email alerts
|

The psychological burden of injury: an 18 month prospective cohort study

Abstract: Objectives: To determine the prevalence of post-trauma psychological problems among a cohort of male accident and emergency department patients admitted to hospital. To identify the changes in their psychological symptoms over an 18 month follow up period. Methods: A prospective cohort study of male accident and emergency department patients who were admitted for treatment of an injury. Baseline interview recorded demographic details and accident details. Standardised questionnaires measured baseline psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
4
46
0
3
Order By: Relevance
“…Injury severity was not associated with the development of later psychopathology in the TCOM study (46), similar to previous studies (13,47,48), and thus it appears that those who drop out are neither at high risk nor at low risk for injury-related PTSD. This finding is similar to that of Mason et al and O'Donnell et al who reported shorter hospital stay as a predictor of dropout (15,16), since those with less severe injuries tend to be discharged shortly after MVA. Participants with less severe injury might consider the MVA unimportant and therefore might tend to be indifferent to this kind of follow-up study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Injury severity was not associated with the development of later psychopathology in the TCOM study (46), similar to previous studies (13,47,48), and thus it appears that those who drop out are neither at high risk nor at low risk for injury-related PTSD. This finding is similar to that of Mason et al and O'Donnell et al who reported shorter hospital stay as a predictor of dropout (15,16), since those with less severe injuries tend to be discharged shortly after MVA. Participants with less severe injury might consider the MVA unimportant and therefore might tend to be indifferent to this kind of follow-up study.…”
Section: Discussionsupporting
confidence: 81%
“…showed that those who dropped out had higher levels of anxiety and depression (16), and Mason et al showed they tend toward psychoticism (15). This apparent contradiction requires elucidation.…”
Section: Objectives Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate hypothesis is that PTSD, which is common in combat casualties, 5 modulates this effect either directly via an inflammatory response 27 or indirectly via weight gain 28 and substance abuse. 6 However, work examining the correlation between ISS and PTSD is conflicting, 29,30 which suggests that this alone cannot account for the differences observed. It is also possible that more severely injured patients have more severe functional limitations resulting in poor outcomes.…”
Section: Iss and Outcomesmentioning
confidence: 99%
“…These propositions are supported by the literature indicating that when psychiatric disorders are co-morbid with traumatic injury, the associated disability is substantial. Many studies, including our own, have uncovered psychiatric disorders (Mason, Wardrope, Turpin, & Rowlands, 2002;Read et al, 2004) and disability after injury (Maraste, Persson, & Berntman, 2003;Smith et al, 2005) and demonstrated that psychiatric morbidity is a major contributor to this disability (Michaels et al, 2000).…”
Section: Introductionmentioning
confidence: 99%